Lipid Profile of Under-5 Years Children from a Tertiary Care Centre - Ghosh Roy, Manisha; Shrivastava, Jyotsna; Bhattacharya, Deepanjan; Agrawal , Amit (Indian Journal of Child Health, 2025)
Introduction: There is a considerable lack of study estimating lipid profile levels in children below 5 years of age. We therefore carried out this cross-sectional study to evaluate the lipid profile level of healthy Indian children under five years of age from a tertiary level hospital in India. Methodology: This observational cross-sectional study was conducted in a tertiary care center. We randomly enrolled 119 healthy children aged 1 month to 5 years, in whom Total cholesterol, triglyceride, HDL, LDL, and VLDL were measured in a random venous blood sample via a BA400 automatic analyzer by BioSystems using Glycerol Phosphate Oxidase/Peroxidase method using the principle of spectrophotometry. Total cholesterol was calculated as the sum of all the lipids detected. Results: Median age was 16 months (9.5 months - 28 months), and 59.6% were male. The overall mean reference range for Total cholesterol was 132.6±38.3 mg/dL, Triglycerides was 98.5±46.2 mg/dL, LDL was 71.5±25.0 mg/dL, HDL was 42.6±15.8mg/dL and VLDL was 19.6±9.3mg/dL. There was no significant difference in lipid profiles between the sexes. HDL level was significantly higher in those above 24 months (p=0.02), while the other components were similar between various age groups. Conclusion: There was no significant difference between the lipid profile of children in our cohort, and previously published studies. Levels of HDL cholesterol increased with age after 24 months of age.